Etymology of the Anthroponyms "Alpamish" and "Barchin" Versions of the Epic "Alpаmish - Anvar Buranov (European Science Publishing, 2023)
This article will discuss the use and etymology of the anthroponyms “Alpаmish” and “Barchin” in the versions of the epic “Alpаmish”. The author expressed his comments in it and presented his conclusions based on a comparative analysis of the variants of the names “Alpomish” and “Barchin”, given in the Uzbek, Kazakh, Karakalpak, Altai, Tatar and Bashkir versions.
Keywords: onomastics, anthroponymy, Alpamish, Barchin, epic, eponymy, comparative studies.